Interview: Elidio La Torre Lagares teaches, Department of Comparative Literature, University of Puerto Rico, Río Piedras - Iris Mónica Vargas (Social Medicine Publication Group, 2020)
Interview between a medical student who was an activist in the protests, with Elidio la Torre Lagares, essayist, narrator, poet and professor of literatura and literary creation at the Faculty of Humanities, University of Puerto Rico.